Strategies for improving the performance of public relations officers based on tri hita karana in the regional office of the Ministry of Religious Affairs of Bangli Regency - Ersania, Ni Luh (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: This study focuses on improving the performance of public relations (Pranata Humas) at the Regional Office of the Ministry of Religious Affairs in Bangli Regency, using the Tri Hita Karana philosophy as a framework. Tri Hita Karana is a Balinese concept emphasizing harmonious relationships between humans, God, others, and nature. Pranata Humas plays a key role in disseminating information about government programs and activities to the public, but faces challenges such as a lack of understanding of Tri Hita Karana and limited community engagement. Methods: The study employs a strategic approach, which includes in-depth education and training for public relations staff on the values of Tri Hita Karana, strengthening collaboration with local communities and NGOs, and leveraging information technology and social media to improve outreach. Findings: The proposed strategies are expected to enhance the understanding of local cultural values among public relations personnel, foster stronger community involvement in government-promoted activities, and improve information dissemination using modern communication tools. Conclusion: By implementing these strategies, the performance of Pranata Humas can be significantly improved, leading to better communication between the government and the public, while promoting harmonious local cultural values. Novelty/Originality of This Study: This research introduces the integration of Tri Hita Karana, a unique Balinese cultural philosophy, into public relations strategies within a government institution, aiming to improve both performance and cultural alignment in public communication efforts.